Oxidative Tea Polyphenols Greatly Inhibit the Absorption of Atenolol - Shan, Yun; Zhang, Mengmeng; Wang, Tengfei; Huang, Qin; Yin, Dan; Xiang, Zemin; Wang, Xuanjun; Sheng, Jun (Frontiers in Pharmacology, 2016)
Oxidative tea polyphenols (OTP) is the oxidative polymerization product of epigallocatechin-3-O-gallate (EGCG) forms during the process of Pu-er tea fermentation, and possesses absorption property, which may absorbs on drugs thus impact the drug bioavaiability when taking medicines with Pu-er tea. Here we demonstrated that OTP inhibited the absorption of atenolol in the intestine, which was determined by testing atenolol levels of plasma via high performance liquid chromatography (HPLC). After administration of atenolol (50mg/kg), atenolol was absorbed (Tmax: 1.867 h) with the half-life (t1/2) of 6.663 h in control group; Compared with atenolol group, AUC0-t(h*ng/ml), AUC0-∞(h*ng/ml) and Cmax of OTP+atenolol group (OTP 500mg/ml + atenolol 50mg/kg) reduced 38.7%, 27% and 51%, respectively, the atenolol concentration of plasma was reduced by OTP approximately 43%, 49% and 55.5% at 30min, 1h and 2h, respectively(P<0.01). Furthermore, the level of atenolol in feces was higher in the OTP+atenolol group, indicating that the absorption of atenolol in rats was inhibited by OTP. Isothermal titration calorimetry (ITC) assay identified that EGCG can bind to atenolol and the in vitro results showed that OTP absorbed on atenolol and formed precipitate in acid condition, demonstrating a significant positive relationship between atenolol levels and OTP dosage. Taken together, these results suggested that consuming Pu-er tea with atenolol might inhibit atenolol absorption and possible other drugs.